The Role Of Post-Production In Affecting Mood Of Hybrid Animation - Wee, Jasmine Shu Ping (Universiti Malaysia Sarawak (UNIMAS), 2019)
The study shows the role of post-production process in affecting mood of hybrid animation. The goal of this study is to identify the post-production process and investigate the technique and skill in post-production process for more effective mood stimulation. The research will be conducted by qualitative method for data collection, through open-ended questionnaire, video-based observation and experimental testing. This study will be used as a guideline for beginner of animator on conducting post-production process for hybrid animation. Besides that, this study also can be used to portray the important of post-production process in hybrid animation as it is a process that communicate the mood of animation towards audiences.